Evaluating Work-Function and Composition of ErSix on Various Surface Orientation of Silicon. (1st January 2016) - Teramoto, Akinobu; Tanaka, Hiroaki; Suwa, Tomoyuki; Goto, Tetsuya; Kuroda, Rihito; Motoya, Tsukasa; Kawase, Kazumasa; Sugawa, Shigetoshi
Abstract : The work function of ErSiX on different surface orientation of Si was evaluated. ErSiX was formed by suppressing of the oxidation during the Si surface cleaning, Er sputtering, and silicidation annealing. Almost ideal Schottky diode properties are obtained on every surface orientation. The work function of ErSiX depends on the surface orientation and deposited Er thickness. The work function of ErSiX on Si(100) decreases and that on Si(551) increases with the increasing Er thickness. In addition, the work function ErSiX on Si(111) for the thickness less than 5 nm is constant and very low value of about 0.25 eV. These work function values depend on Si concentration in ErSiX, and it is considered that the concentration difference is caused by the lattice mismatch between ErSi2 and Si surface.